Lithuanian Jewish in 1941-1945: continuation of holocaust in Stutthoff concentration camp - Buchaveckas, Stanislovas (Genocidas ir rezistencija, 2020)
Some of the Lithuanian Jews who survived the end of 1941, imprisoned and held in ghettos and labour or concentration camps, managed to stay alive until the summer of 1944 only to be sent to the Stutthof concentration camp as the German army was retreating from the Baltic States (Ostland). The fate of the Lithuanian Jews who survived the mass killings of the summer and autumn of 1941 and ended up in this place of suffering and death (next to the beautiful sandy beaches of the Baltic Sea, 3 km away from the Forest of Gods concentration camp) was different from with the winter of 1941–1942. It varied considerably even in the same ghetto, where isolated Jews were imprisoned during the period of so-called conditional stabilisation (from the end of 1941). Subsequently, the possibility of saving the life of a surviving Lithuanian Jewish Litvak family, several of its members, or at least one person, depended on various circumstances. These varied both within the ghetto itself and in the labour camps set up near the ghetto, in the form of companies operating in the surrounding settlements.